COMMUNICATION PATTERNS AMONG K-POP FAN GROUPS IN THE DIGITAL AGE (A STUDY OF THE TREASURE MAKER PEKANBARU SOCIAL MEDIA GROUP) - Fenny Anita; Wika Apriliayana; Muhamadd Hanif Ahda (Universitas Dharmawangsa Medan, 2026)
The development of digital technology has created new spaces for interaction that encourage the formation of fandom communities through social media. One active community in Pekanbaru is Treasure Maker (Teume), a fandom of the K-Pop boy group Treasure that uses Instagram and WhatsApp as its main communication platforms. This study aims to identify the group communication patterns of the Treasure Maker Pekanbaru community in the digital era. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving administrators, active members, and passive members selected purposively. Data analysis uses Communication Network Theory with the indicators of density, centrality, and pattern of ties. The findings show that the community applies a hybrid communication pattern, combining centralized and two-way communication. Administrators act as the center of the communication network, active members contribute to two-way interactions, while passive members mainly receive information. This communication pattern enables the Treasure Maker Pekanbaru community to effectively disseminate information, maintain member connectedness, and strengthen its existence in the digital era.